Evaluation the higher education: a study of the determinants of performance - Alessandro Lepchak; André Júnior de Oliveira; Adriana Fragalli; Jorge Eduardo Scarpin (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Given the demands of society, there is the evolution of investment in higher education in recent years in Brazil. The aim of the study was to identify factors that influence the performance indicators of higher education. Data were collected through the websites of government agencies. The methodology used was quantitative, using multiple linear regression. The sample was composed by 52 federal universities and the analysis period 2009-2011. The results indicate that the variable 'cost per student' influences the IGC in all periods. The indicators ENADE e CPC are influenced by the 'number of students' only in 2009.